2006
DOI: 10.1038/sj.pcan.4500881
|View full text |Cite
|
Sign up to set email alerts
|

More effects of extracorporeal magnetic innervation and terazosin therapy than terazosin therapy alone for non-inflammatory chronic pelvic pain syndrome: a pilot study

Abstract: The objective of this study was to evaluate whether extracorporeal magnetic innervation (ExMI) combined with a-blocker therapy is more effective than a-blocker monotherapy for patients with non-inflammatory chronic prostatitis (CP)/chronic pelvic pain syndrome (CPPS), category IIIB. Patients were randomized to either terazosin monotherapy (group 1, n ¼ 21) or terazosin combined with ExMI therapy (group 2, n ¼ 19). Patients in group 2 had 12 treatment sessions of ExMI twice a week during 6 weeks. None of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…[8] While all 35 studies were randomized, only 14[18], [22]–[24], [26], [29][34], [43]–[45] were categorized as randomized appropriately on the Jadad system (Table S3). Of the 35 randomized studies, 21[18]–[24], [26][37], [44], [50] were blinded and 19[18]–[24], [26], [28], [30][37], [44], [50] were blinded appropriately.…”
Section: Resultsmentioning
confidence: 99%
“…[8] While all 35 studies were randomized, only 14[18], [22]–[24], [26], [29][34], [43]–[45] were categorized as randomized appropriately on the Jadad system (Table S3). Of the 35 randomized studies, 21[18]–[24], [26][37], [44], [50] were blinded and 19[18]–[24], [26], [28], [30][37], [44], [50] were blinded appropriately.…”
Section: Resultsmentioning
confidence: 99%
“…The mean symptom scores decreased significantly in the actively treated group at 3 months and 1 year (P<0.05); the greatest improvement was in pain-related symptoms [77]. In 2006, Paick et al [78] showed that extracorporeal magnetic innervation combined with α-blocker therapy may be more effective than α-blocker monotherapy for patients with CP/CPPS.…”
Section: Electromagnetic Therapymentioning
confidence: 95%
“…Paick et al [ 16 ] combined extracorporeal magnetic innervation (ExMI) with α -blocker therapy (group 1; n = 21) to determine if it were more effective than α -blocker monotherapy (group 2; n = 19) for patients with CPPS (category IIIb). Patients in group 2 had 12 treatment sessions of ExMI for 6 weeks.…”
Section: Electromagnetic Therapymentioning
confidence: 99%